Analysis of the Priirtysh Sedimentary Basin for the Presence of Aquifers Suitable for CO2 Storage - Nuranbayeva, Bulbul; Logvinenko, Alexandr; Kenessary, Abzal; Abishev, Daniyar; Shamiev, Nurbek; Tyulebayeva, Ranida; Samigatova, Saida (Engineering, Technology & Applied Science Research, 2025)
This scientific study presents a comprehensive assessment of the Priirtysh sedimentary basin, focusing on identifying potential reservoirs for carbon dioxide (CO₂) storage. The methodology includes 2D seismic data interpretation, well log analysis, and the construction of a 3D geological model using Petrel software. Seismic surveys conducted between 1992 and 1997, along with data from more than 4,000 hydrogeological wells, were utilized to develop a structural and lithological model of the basin. Kazakhstan currently lacks dedicated infrastructure for CO₂ capture and storage. Notably, potential CO₂ storage formations in the Pavlodar region, which accounts for the highest greenhouse gas emissions in the country, have yet to be systematically evaluated. Thus, investigating the CO₂ storage potential of regional aquifers is of both scientific and strategic importance. By combining geophysical (seismic interpretation) and petrophysical (porosity, permeability, and reservoir quality) analyses with 3D geological modeling, this study offers new insights into the subsurface architecture of the basin. The integration of seismic and well log data significantly enhances the model’s accuracy and enables the identification of structural complexities. Key findings indicate the presence of several promising aquifers at depths between 500 and 2,000 m, particularly within the Upper Jurassic–Cenozoic formations. The study estimates the CO₂ storage capacity of these aquifers and assesses their suitability for long-term containment, laying the groundwork for future hydrodynamic simulations and injection feasibility studies. Ultimately, the identification of viable storage formations in the Pavlodar region aligns with Kazakhstan’s strategic goal of achieving carbon neutrality by 2060.